Decreased Global Network Efficiency in Young Male Smoker: An EEG Study during the Resting State - Su, Shaoping; Yu, Dahua; Cheng, Jiadong; Chen, Yajing; Zhang, Xiaohua; Guan, Yanyan; Li, Yangding; Bi, Yanzhi; Xue, Ting; Lu, Xiaoqi; Yuan, Kai (Frontiers in Psychology, 2017)
Previous electroencephalogram (EEG) studies revealed reduced spectral power during the resting state in smokers. However, few studies investigated the changes of global brain networks during the resting state in young smokers by EEG. In the present study, we used minimum spanning tree (MST) to assess the differences of global network efficiency between young smoker (n=20) and nonsmokers (n=20).Compared with healthy nonsmokers, young smokers showed decreased leaf fraction, kappa value, increased diameter and eccentricity value in alpha band (r = 0.574, p = 0.008), which suggested the global network efficiency was decreased in young smokers. We also found positive correlation between leaf fraction and onset time of smoking in smokers. These results provided more scientific evidence of the abnormal neural oscillations of young smokers and improved our understanding of smoking addiction.